2011
DOI: 10.1017/s0022149x10000878
|View full text |Cite
|
Sign up to set email alerts
|

In vitroinduction of lymph node cell proliferation by mouse bone marrow dendritic cells following stimulation with differentEchinococcus multilocularisantigens

Abstract: The immune response of mice experimentally infected with Echinococcus multilocularis metacestodes becomes impaired so as to allow parasite survival and proliferation. Our study tackled the question on how different classes of E. multilocularis antigens (crude vesicular fluid (VF); purified proteinic rec-14-3-3; purified carbohydrate Em2(G11)) are involved in the maturation process of bone-marrow-derived dendritic cells (BMDCs) and subsequent exposure to lymph node (LN) cells. In our experiments, we used BMDCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…In this regard, ferritin is a more potent inducer of DC maturation, expression of co-stimulatory molecules and increasing migration capacity than is LPS. Our result is consistent with that of Jene (Jenne et al 2001) and Margos (Margos et al 2011). They found that DCs in presence of the Echinococcus multilocularis 14-3-3 antigen transform into mature DC that were slightly more effective inducers of T-cell proliferation than DC exposed to crude non-fractionated E. multilocularis antigen or Em2 (G11) antigen.…”
Section: Discussionsupporting
confidence: 95%
“…In this regard, ferritin is a more potent inducer of DC maturation, expression of co-stimulatory molecules and increasing migration capacity than is LPS. Our result is consistent with that of Jene (Jenne et al 2001) and Margos (Margos et al 2011). They found that DCs in presence of the Echinococcus multilocularis 14-3-3 antigen transform into mature DC that were slightly more effective inducers of T-cell proliferation than DC exposed to crude non-fractionated E. multilocularis antigen or Em2 (G11) antigen.…”
Section: Discussionsupporting
confidence: 95%
“…The mechanisms underlying this association may involve regulatory cells and cytokines. Our research found that the proportion of CD4 + CD25 + FOXP3+ Treg cells relative to CD4+ Treg cells increased after E. granulosus infection was consistent with previous studies [ 21 ] and significantly increased with preliminary treatment with DEX, which suggested their possible role to contributed to the maintenance of immune tolerance. However, the proportion of Treg cells relative to CD4+ cells was reduced in untreaded mice when allergic reaction happened,just as previously described [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, LPS and Em14-3-3 yielded elevated IL-12, TNF-I+/-and IL-10 expression levels, while Em2(G11) did not. The proliferation of bone marrow DC isolated from AE-diseased mice was abrogated (Margos et al, 2011), indicating the E. multilocularis infection inhibited T cell responses.…”
Section: Dendritc Cellsmentioning
confidence: 99%